ChemInform Abstract: Activation of DMSO for Swern‐Type Oxidation by 1, 1‐Dichlorocycloheptatriene. Issue 18 (May 2015) - Nguyen, Thanh Vinh; Hall, Michael
Abstract The operationally simple method is efficiently applied to primary and secondary benzylic and aliphatic alcohols.